Immune profiling and functional analysis of NK and T cells in ataxia telangiectasia - Graafen, Lea; Heinze, Annekathrin; Albinger, Nawid; Salzmann-Manrique, Emilia; Ganß, Franziska; Hünecke, Sabine; Cappel, Claudia; Wölke, Sandra; Donath, Helena; Trischler, Jordis; Theilen, Till-Martin; Heller, Christine; et al. (Frontiers in Immunology, 2024)
• In a large cohort of AT patients (n=65) we observed reduced levels of B cells, CD4 + and CD8 + T cells and no difference in the amount of NK and NKT cells in peripheral blood compared to age-matched reference values• Longitudinal evaluation of immune cell counts in the same AT cohort did not predict the subsequent development of malignancies.• Extended immune phenotyping indicates altered expression of death receptor ligands and CD16 in stimulated NK cells together with a higher activation level of T cells in AT, demonstrated in the increased expression of CD107a, TRAIL and FasL.